The Relationship Between Financial Wellness and Job Performance in Employees of PDAM Tugu Tirta in Malang City - Mustafa, Mifta Ihza Zahwa; Chusniyah, Tutut; Bimantoro, Demanda (Universitas Negeri Malang, 2024)
Job performance is a crucial criterion related to organizational outcomes and success. One of the factors that influence job performance is individual financial wellness. This research examines the relationship between financial wellness and job performance among employees of PDAM Tugu Tirta in Malang City. This research utilized a quantitative, non-experimental correlational method. The sample consisted of 100 employees of PDAM Tugu Tirta in Malang City, selected using an accidental sampling technique. The instruments employed were the Personal Financial Wellness Questionnaire and the Individual Job Performance Questionnaire. The data analysis involved the use of Pearson's product-moment correlation analysis. The analysis results indicate that financial wellness has a significant positive relationship with job performance (rxy equals .662; Sig. equals 0.00).